My story, my dance : Robert Battle's journey to Alvin Ailey - Cline-Ransome, Lesa (Simon & Schuster Books for Young readers, 2015)
A boy discovers his passion for dance and becomes a modern hero in this inspiring picture book biography of Robert Battle, artistic director of the Alvin Ailey American Dance Theater.